Interjections in the Contexts of Uzbek and English Languages - N. N. Salikhova (Indonesian Journal of Innovation Studies, 2022)
The hereby article discusses the main differences and similarities of Uzbek and English interjections in terms of their usage, types, morphology, functions etc. All the findings are evinced with the valid examples taken from the reliable sources.